Employment, Economic Condition and Satisfation Levels: A Micro Level Analysis of Construction Workers in Gulbarga City - Anil Kumar B. Khote (2013)
The paper attempts to analyse the employment condition of construction workers in Gulbarga city. The construction activities in Gulbarga have increased a great deal since the last three years. The upcoming mechanisation and introduction of new technology and the coming of migrated labours in this sector were reducing employment opportunities for construction workers in the city (both male and female). Hence, a study of this sector was very important to get an insight of the present working condition of construction workers in Gulbarga city. It was also important to ascertain the number of days the workers were getting employment on construction sites. An attempt was made to explore the social security measures taken by the contractors for the construction workers and the level of satisfaction of the workers with respect to the wages received by them. The paper highlights major findings of the study and recommends certain policy initiatives for the socio–economic upliftment of the construction workers.